2019
DOI: 10.46252/jsai-fpik-unipa.2019.vol.3.no.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Distribution of Gastropods In Rocky Intertidal Area In North Manokwari, West Papua

Abstract: Gastropods is an important organism that commonly found inhabiting the rocky intertidal area. Distribution pattern of this species is influenced by various factors such as population history, microhabitat, predation and a complex interactions between oceanographic dynamics and ecological features. This study aims to compare the temporal distribution pattern of gastropods at two different rocky intertidal area. This research was conducted at the rocky intertidal area of Amban and Nuni, North Manokwari District,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
0
7
0
4
Order By: Relevance
“…The study on the coastal area of Liki Islarmi collected 1812 gastropods, with a range of 182-603 individual gastropods within 6 sampling stations, consisting of 63 species of gastropods from 23 families (Table 2). This species' number and distribution showed that gastropods have a very wide distribution area and are often found in intertidal areas (Saleky et al 2019;Susintowati et al 2019). The community structure of gastropods was strongly influenced by changes in environmental factors (Hitalessy et al 2015;Septiani and Wiharyanto 2015;D'Souza et al 2022).…”
Section: Community Distribution Of Gastropodmentioning
confidence: 85%
See 1 more Smart Citation
“…The study on the coastal area of Liki Islarmi collected 1812 gastropods, with a range of 182-603 individual gastropods within 6 sampling stations, consisting of 63 species of gastropods from 23 families (Table 2). This species' number and distribution showed that gastropods have a very wide distribution area and are often found in intertidal areas (Saleky et al 2019;Susintowati et al 2019). The community structure of gastropods was strongly influenced by changes in environmental factors (Hitalessy et al 2015;Septiani and Wiharyanto 2015;D'Souza et al 2022).…”
Section: Community Distribution Of Gastropodmentioning
confidence: 85%
“…These species were commonly encountered in intertidal areas and showed adaptation to the substrate type and other environmental factors. One of those species, Monetaria annulus, usually known as 'ring cowrie,' is normally found in the intertidal and inhabits sandy and muddy -coastal areas, as well as reef flats with seagrasses or coral fractures (Aji et al 2018;Saleky et al 2019). The presence of the gastropods community and their distribution patterns generally occur because of the variability of environmental factors such as nutrition availability, substrate type, associations with other species, temperature and pH condition, and also oxygen content.…”
Section: Community Distribution Of Gastropodmentioning
confidence: 99%
“…(Srimariana, 2015). T. setosus kebanyakan hidup pada daerah intertidal berbatu (Baharuddin, Basir, & Zainuddin, 2019;Saleky et al, 2019).…”
Section: Analisis Molekulerunclassified
“…Hewan ini dapat mencapai ukuran 6 -7 cm dan berada di perairan yang tenang (Dharma, 2005) dan dapat ditemukan pada daerah intertidal berbatu di pesisir utara. Spesies T. setosus sering ditemukan hidup bersama dengan spesies lain seperti T. sparverius dan T. bruneus (Saleky et al, 2019(Saleky et al, , 2016.…”
Section: Hubungan Panjang Berat Dan Pola Pertumbuhanunclassified
“…Kata kunci: Cerithidea anticipata; Gen COI; DNA barcoding; filogenetik PENDAHULUAN Gastropoda Potamidae merupakan kelompok gastropoda yang sangat melimpah dan hidup pada ekosistem mangrove (Ratsimbazafy and Kochzius, 2018). Lebih dari 25 spesies gastropoda Potamidae melimpah pada ekosistem mangrove (Reid et al, 2008) yang penyebarannya sangat dipengaruhi oleh kondisi fisik-kimia perairan, subtrat dasar dan juga kondisi microhabitat (Saleky et al, 2019;Syahrial et al, 2020).…”
unclassified